Data from: Humpback whales blow poloidal vortex bubble rings ... - Sharpe, Fred; Frediani, Jodi; Hubbard, Josephine; Perrine, Doug; McCowan, Brenda; Hilbourne, Simon; Reidenberg, Joy; Doyle, Laurance (Dryad, 2023)
Among mysticetes, humpback whales (Megaptera novaeangliae) make extensive use of bubbles (bursts, trails, curtains) for display by combative breeding males and to create barrier traps (nets, clouds) when hunting schooling prey. Here we describe another genre of air release, the bubble ring, a donut-shaped, poloidally spinning, air-infused, vortex (analogous to a “smoke ring”). Bubble rings are well described among aquaria housed dolphins, but scantily reported among the mysticetes. We reviewed bubble ring production in eleven individuals that were documented by naturalists, citizen scientists and researchers on both the feeding and breeding grounds across three oceans. In cases where observable, humpback bubble rings were produced from one nostril, indicating considerable blowhole dexterity. The context of bubble ring production is described for each episode, including the orientation and distance to the closest object in the water (boat, swimmer or another whale). We consider a variety of possible functions ... : Field observations used in this study were made by naturalists, citizen scientists and researchers with whom we conducted interviews and analyzed their video footage (8 episodes) or photos (4 episodes). Observations were made opportunistically and obtained from a private vessel, two research vessels, two whale swim vessels, one commercial and one private, three commercial whale watch vessels and two light airplanes. Whenever possible, a still photo or screen capture was obtained of the ventral side of the flukes for comparison with regional fluke photo-identification catalogs. The data collected (i.e. episodes of bubble ring production) were not processed, and remain in raw form as collected from the observers. In some cases, we extracted still photos from the videos provided to highlight the ring production component of the encounter. Table 2 is a summary of all twelve encounters. ...